Pengaruh Implementasi Metode Pembelajaran Teams Games Tournaments terhadap Variabel Motivasi, Minat Belajar, dan Hasil Belajar Peserta Didik pada Mata Pelajaran Desain Grafis Percetakan di SMK Negeri 12 Malang - Rahmawati Hari Khasanah; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
This research background is the lack of student participation, learning methods that have not been able to increase motivation to learn, and the lack of students' interest in learning. This study aims to show whether the implementation of Teams Games Tournaments learning methods has an influence on the variables of student motivation, learning interest, and student learning outcomes at SMK Negeri 12 Malang. The method in this research use Quasi Experimental and Nonequivalent Control Group Design. The data collection by observation and interview. The result of the data analysis in the research experiment are: (1) Method of TGT did not influence the students' motivation, (2) Methods of TGT influenced the students' interest, (3) Method of TGT influenced the students' learning outcomes. Therefore it can be concluded that learning method implementation of Teams Games Tournament does not influence the learning method, but influences the interest and learning outcomes of the students.